Pemberdayaan Masyarakat Dalam Pemasaran Produk Industri Rumah Tangga Melalui Penerapan E-Commerce Di Kenagarian Vii Koto Talago Kecamatan Guguak Kabupaten 50 Kota - Elfizon Elfizon; Ganefri Ganefri; Asrul Huda (JTEV (Jurnal Teknik Elektro dan Vokasional), 2020)
This paper aimed to provide an understanding of the importance of increasing competence in using the internet as a medium for marketing and promoting the results of household industry products that it engages in through e-commerce. Strategic approaches used in the implementation of activities. community service is in the form of face-to-face strategy and training, where the implementers of this activity come to the location of the activity in providing training materials. The material and the exercises are arranged with the concept as simple as possible, so that participants can explore more deeply through exercises and questions and answers with the instructor throughout the training process. During the training participants can discuss problems encountered under the direction and guidance of the instructor, especially those related to the material presented. The results of the activity are expected to have a positive impact on the community, especially home industry entrepreneurs who are able to create and implement e-commerce in marketing and promoting home industry businesses in Kenagarian VII Koto Talago Kec. Guguak Kab. Lima Puluh Kota.